Dental pulp stem cells: Potential significance in regenerative medicine - Todorović Vera; Marković Dejan; Milošević-Jovčić Nadežda; Petakov Marijana; Balint Bela; Čolić Miodrag; Milenković Ana; Čolak Ivana; Jokanović Vukoman; Nikolić Nebojša (Serbian Medical Society - Dental Section, Belgrade, 2008)
To date, three types of dental stem cells have been isolated: Dental Pulp Stem Cells (DPSC), Stem Cells From Human Exfoliated Deciduous Teeth (SHED) and Immature Dental Pulp Stem Cells (IDPC). These dental stem cells are considered as mesenchymal stem cells. They reside within the perivascular niche of dental pulp. They are highly proliferative, clonogenic, multipotent and are similar to mesenchymal Bone Marrow Stem Cells (BMSC). Also, they have high plasticity and can be easy isolated. The expressions of the alkaline phosphatase gene, dentin matrix protein 1 and dentinsialophosphoprotein are verified in these cells. Analyses of gene expression patterns indicated several genes which encode extracellular matrix components, cell adhesion molecules, growth factors and transcription regulators, cell signaling, cell communication or cell metabolism. In both conditions, in vivo and in vitro, these cells have the ability to differentiate into odontoblasts, chondrocytes, osteoblasts, adipocytes, neurons, melanocytes, smooth and skeletal muscles and endothelial cells. In vivo, after implantation, they have shown potential to differentiate into dentin but also into tissues like bone, adipose or neural tissue. In general, DPSCs are considered to have antiinflammatory and immunomodulatory abilities. After being grafted into allogenic tissues these cells are ableto induce immunological tolerance. Immunosuppressive effect is shown through the ability to inhibit proliferation of T lymphocytes. Dental pulp stem cells open new perspectives in therapeutic use not only in dentin regeneration, periodontal tissues and skeletoarticular, tissues of craniofacial region but also in treatment of neurotrauma, autoimmune diseases, myocardial infarction, muscular dystrophy and connective tissue damages.